Dakwah Harmoni Sebagai Solusi Problem Agama dan Modernisme Perspektif Djohan Effendi - Munir, Muhammad Munir; Ahmad Muqaffi (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2020)
Harmony is the need of all people in this world, so in making a growing exchange and interaction between religions and a stronger tendency towards religious diversity will present a new opportunity and challenge for harmony in religious relations. As a result, exchanges between various religions occur more frequently, more opportunities are provided for religions to conduct joint learning and strengthen cooperation. In the experience of all mankind, especially in several countries and regions in the east, from various events that occur gathered a lot of experience and wisdom in terms of cultural diversity, In this study will be discussed about how the propagation of harmony exemplified by Djohan Effendy, to make this research more specifically then, in this issue we are interested in describing and identifying the thought of the propaganda of harmony Djohan Effendi. This study aims to find the propaganda of harmony in social life. This research is a library research that aims to understand and apply the propaganda exemplified by Djohan Effendi. The focus is his thoughts on the da'wah hormoni. The approach used is a historical method. This approach is used to observe and trace the process of forming ideas and thoughts of a character based on the socio-cultural context of his life. The results of this study found 1) The Concept of Religious Pluralism as a Solution of Harmony Harmony According to Djohan Effendi, 2) Da'wah Harmoni Djohan Effendi.